2016
DOI: 10.2147/ndt.s118326
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous brain activity pattern in patients with high myopia using amplitude of low-frequency fluctuation: a resting-state fMRI study

Abstract: ObjectiveMany previous reports have demonstrated significant neural anatomy changes in the brain of high myopic (HM) patients, whereas the spontaneous brain activity changes in the HM patients at rest are not well studied. Our objective was to use amplitude of low-frequency fluctuation (ALFF) method to investigate the changes in spontaneous brain activity in HM patients and their relationships with clinical features.MethodsA total of 38 patients with HM (17 males and 21 females) and 38 healthy controls (HCs) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 47 publications
1
40
1
Order By: Relevance
“… 19 , 20 Furthermore, studies on diverse types of strabismus also exhibited abnormal activity in specific regions of the brain both under tasking state and resting state. 21 23 However, previous studies have only focused on the strabismus or amblyopia, respectively.…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 Furthermore, studies on diverse types of strabismus also exhibited abnormal activity in specific regions of the brain both under tasking state and resting state. 21 23 However, previous studies have only focused on the strabismus or amblyopia, respectively.…”
Section: Introductionmentioning
confidence: 99%
“… 23 And a previous study showed lower ALFF values can be detected in the right IFG region of severe myopia patients. 24 And as we recorded the similar tendency of neuronal activities, it could be concluded that visual deficiency still occurred even for patients who took Lasik surgery. Thus, the Lasik surgery just partially corrected visual deficiency rather than fully compensated the visual impairment.…”
Section: Discussionmentioning
confidence: 68%
“…The majority of previous studies compared nearsighted patients with healthy groups who were matched with age, sex, and educational status to subjects. 12 , 13 Guo et al 12 pointed out that, in high myopia patients compared with 20-paired subjects, decreased ALFF was observed in the bilateral frontal lobe, the right inferior parietal lobule, and the left occipital lobe, while increased ALFF values were in the left caudate nucleus, the occipital lobe, and the thalamus. Besides, Huang et al 13 discovered the altered regions in high myopia patients that were significantly lower ALFF in the middle temporal gyrus, left inferior frontal gyrus/putamen, right inferior frontal gyrus/putamen/insula, right middle frontal gyrus, and right inferior parietal lobule, and higher ALFF values in the bilateral midcingulate cortex, left postcentral gyrus, and left precuneus/inferior parietal lobule.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zhai et al 17 reported that HM patients have a decreased long-range functional connectivity density in the inferior temporal gyrus, the supramarginal gyrus, and the rostrolateral prefrontal cortex. In our previous study, we found that HM patients showed low-frequency fluctuations with an abnormal amplitude in many brain regions related to language understanding and attentional control 18 . However, the above-mentioned studies focused on the alterations in brain function activities.…”
Section: Introductionmentioning
confidence: 94%